Role and Responsibility of Notaries in Making of Authentic Deed Role and Responsibility of Notaries in Making of Authentic Deed for Registration Electronic Fiduciary Guarantee (Online System)for Registration Electronic Fiduciary Guarantee (Online System) - Dian Melinda Oktavia (International Journal of Latin Notary, 2021)
In principle, the strength attached to the Authentic Deed made by a Notary is perfect(volledig bewijskracht) and binding (bindende bewijskracht), provided that the deed has metformal and material requirements. Given the importance of the registration function of fiduciarysecurity, the Fiduciary Security Law then regulates it by requiring every fiduciary guarantee tobe registered with the competent authority. The problem that exists is that there is often amismatch between the Fiduciary Guarantee Deed and the condition of the object which is theobject of the Fiduciary Guarantee when an electronic registration of the Fiduciary Guarantee iscarried out. Based on these problems, the authors identified several problems as follows: 1) Whatis the legal basis regarding the role of the Notary in making deeds and registering fiduciarysecurity electronically (online system); 2) What is the responsibility of the Notary in issuingauthentic deeds for registration of fiduciary security electronically (online system); and 3) Whatare the obstacles faced by the notary in fulfilling the material truth of the fiduciary guaranteedeed.Specifications research in this thesis is done by analytic descriptive illustrates a problemthat is then assessed and analyzed with the use of primary law, secondary law and tertiary legalmaterials. The method used in this research is normative juridical approach, ie testing andreviewing secondary data. With regard to the normative juridical approach is used, the researchwas conducted in two phases, namely the study of literature and field research are merelysupporting, data analysis used is the analysis of qualitative juridical, ie the data obtained, eitherin the form of secondary data and primary data were analyzed with without using statisticalformulas.The results show that the legal basis for the registration process for fiduciary securityelectronically (online system) refers to the Regulation of the Minister of Law and Human RightsNumber 10 of 2013 concerning Electronic Fiduciary Registration Procedures. The responsibilityof a notary in issuing authentic deeds for registration of fiduciary guarantees electronically(online system) can be fulfilled by examining the correctness of the material and the formal truthof the deeds he has made. Fulfillment of material truth can be obtained from certainty about thematerial of a deed, while formal truth can be obtained from certainty that something of the eventsand facts mentioned in the deed was properly carried out by a notary or explained by the partieswho presented it at the time stated in the deed in accordance with the procedures that have beenspecified in the deed. The obstacle faced by the Notary in fulfilling the material truth of theFiduciary Guarantee Deed is that the Notary does not give the authority by law to carry outchecks / field reviews / investigations on an object of an agreement made in order to fulfill thematerial truth of the documents from the parties.